Biofilm of Antibiotics Resistant Salmonella Typhimurium and Salmonella Enteritidis Against Detergents - Elexson, N. A.; Yaya, Rukayadi; Son, Radu (Transactions on Science and Technology, 2016)
Salmonella is able to produce biofilm which is more resistant toward disinfectants and antibodics than its planktonic form. Salmonella typhimurium from beef and Salmonela Enteritidis from raw vegetables isolates were tested for their susceptibility using 18 different antibiotics. Salmonella typhimurium isolate was resistant toward Streptomycin, Sulfamethoxazole, Penicillin, Erythromycin, Tetracyclin, Ampicillin, Rifampicin and Clarithromycin while Salmonella enteritidis was resistant toward Amikacin, Streptomycin, Penicillin, Cipfoflaxin, Erythromycin, Ampicilin, Tetracyclin, Rifampicin, Cepthalothin, Amikacin, Chloramphenicol and Clarithromycin. Both of Salmonella isolates showed MAR index > 0.2, indicating that these isolates might be originated from high risk sources. Out of the five detergents, Detergent 3 (D3) (Linear alkyl Sulfonic acid was found to be the most effective. The Minimum Inhibition Concentrations (MICs) and Minimal Bactericidal Concentration (MBCs) was ranged from 6250 – 25,000 μg/ml and 25,000 to > 50000 μg/ml, respectively. Biofilm-producing ability of antibiotics -resistant Salmonella typhimurium and Salmonella enteritidis were inhibited at 12,500 – 25,000 μg/ml and eradicated at >50000 μg/ml. Therefore, Detergents showed potential antimicrobial activity against Salmonella.